PROBLEM METHODS OF LEARNING AND ACTIVATION OF COGNITIVE ACTIVITY OF JUNIOR SCHOOLCHILDREN - Nurxida Sabirovna, Zakirova (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2023)
his article is devoted to the place of problematic teaching methods in the activation of the cognitive activity of younger students. Problematic methods in the process of education serve to effectively ensure the organization and activation of the cognitive activity of students.